Computer architecture : a quantitative approach - Hennessy, John L., 1952-; Patterson, David A., 1947- (San Francisco (Calif.) : Morgan Kaufmann, 2003)
Chapter 1 - Fundamentals of Computer Design Chapter 2 - Instruction Set Principles and Examples Chapter 3 - Instruction-Level Parallelism and Its Dynamic Exploitation Chapter 4 - Exploiting Instruction-Level Parallelism with Software Approaches Chapter 5 - Memory Hierarchy Design Chapter 6 - Multiprocessors and Thread-Level Parallelism Chapter 7 - Storage Systems Chapter 8 - Interconnection Networks and Clusters Appendix A - Pipelining: Basic and Intermediate Concepts Appendix B - Solutions to Selected Exercises Online Appendices Appendix C - A Survey of RISC Architectures for Desktop, Server, and Embedded Computers Appendix D - An Alternative to RISC: The Intel 80x86 Appendix E - Another Alternative to RISC: The VAX Architecture Appendix F - The IBM 360/370 Architecture for Mainframe Computers Appendix G - Vector Processors Revised by Krste Asanovic Appendix H - Computer Arithmetic by David Goldberg Appendix I - Implementing Coherence Protocols
Keywords: Computer architecture; Computerarchitectuur